Explaining poverty evolution: The case of Mozambique - Channing Arndt; M. Azhar Hussain; E. Samuel Jones; Virgulino Nhate; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Measuring poverty remains a complex and contentious issue. This is particularly true in sub-Saharan Africa where poverty rates are higher, information bases typically weaker, and the underlying determinants of welfare relatively volatile. This paper employs recently collected data on household consumption in Mozambique to examine the evolution of consumption poverty with focus on the period 2002/03 to 2008/09. The paper contributes in four areas. First, the period in question was characterized by major movements in international commodity prices. Mozambique provides an illuminating case study of the implications of these world commodity price changes for living standards of poor people. Second, a novel 'backcasting' approach using a computable general equilibrium model of Mozambique, linked to a poverty module is introduced. Third, the backcasting approach is also employed to rigorously examine the poverty-growth-inequality triangle. Finally, various simple but useful and rarely applied approaches to considering regional changes in poverty rates are presented. We find that the national poverty rate in Mozambique stagnated between 2002/03 and 2008/09.
Keywords: O10; O13; I32; 330; measurement; poverty; growth; inequality; economy-wide modelling; Armut; Messung; Verbraucherausgaben; Mosambik